2013
DOI: 10.5897/ajmr2013.6028
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Escherichia coli isolated from healthy cattle at a major cattle market in Ibadan, Oyo State, South Western, Nigeria

Abstract: Isolation of multidrug resistant Escherichia coli from diseased livestock is becoming rampart from samples submitted for disease diagnostic purposes in some Tertiary Veterinary Teaching Hospitals in Nigeria. In order to evaluate the possible roles of commensal E. coli from apparently healthy animals in the epidemiology of drug resistant pathogens, antibiotic resistance status of 240 E. coli isolated from 300 rectal swab from apparently healthy cattle from a major cattle market in Ibadan, Oyo State, South West … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
3
5
0
1
Order By: Relevance
“…Our results corroborated with the findings of Ogunleye et al (2013), but much lower than the findings of Masud et al (2012). Differences in geographical locations might be the reason for this as Islam et al (2014) reported a geographical variation in the prevalence of E. coli in cattle.…”
Section: Discussionsupporting
confidence: 92%
“…Our results corroborated with the findings of Ogunleye et al (2013), but much lower than the findings of Masud et al (2012). Differences in geographical locations might be the reason for this as Islam et al (2014) reported a geographical variation in the prevalence of E. coli in cattle.…”
Section: Discussionsupporting
confidence: 92%
“…According to this study prevalence of E. coli was high in cattle ≥3 years of age, female and unorganized farming systems, but the differences were not significant. The overall prevalence as obtained in this study support the findings of Ogunleye et al (2013), who described a prevalence of 80% in the apparently healthy cattle of Nigeria but higher than the prevalence described by the Masud et al (2012). According to Masud et al (2012), the prevalence of E. coli in the rectal swab of apparently healthy cattle of 2-3 years of age is 23.21% in another geographic location in Bangladesh.…”
Section: Discussionsupporting
confidence: 90%
“…These differences might be due to the differences in methodology employed in these studies. Ogunleye et al (2013) and Masud et al (2012) described their findings based on cultural and biochemical examination. In this study, in addition to traditional techniques i.e., morphology, staining, cultural and biochemical test, PCR was employed for the confirmatory identification of E. coli from rectal swab of apparently health cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, most of isolated bacteria was E. coli at the proportion of 85% (72 sample) of total sample and the rest of samples were contained the isolates of other coliforms. Similar results have also been obtained from the study in Nigeria and Bangladesh, both reported the prevalence of E. coli from sample of rectal swab of cattle between 75%-80% [17,18]. Interestingly, both of studies were taken sample from the cattle those assumed healthy.…”
Section: Isolation Of E Colisupporting
confidence: 84%